Smoking bans, maternal smoking and birth outcomes - Prashant Bharadwaj; Julian V. Johnsen; Katrine Vellesen Loken (Institute for the Study of Labor (IZA), 2012)
An important externality of smoking is the harm it might cause to those who do not smoke. This paper examines the impact on birth outcomes of children of female workers who are affected by smoking bans in the workplace. Analyzing a 2004 law change in Norway that extended smoking restrictions to bars and restaurants, we find that children of female workers in restaurants and bars born after the law change saw significantly lower rates of being born below the very low birth weight (VLBW) threshold and were less likely to be born pre-term. Using detailed data on smoking status during pregnancy, we find that relative to the control group, most of the benefits arise from changes in smoking behavior of the mother; the effect of second hand smoke exposure on birth outcomes in this formulation appears to be quite small. However, we find suggestive evidence of substituting behavior, i.e. a greater likelihood of smoking at home among fathers, since children born to male workers in restaurants and bars after this law change appear to have slightly worse outcomes. Using individual tax data, we find that the law change did not result in changes in earnings or employment opportunities for those affected, thus suggesting that the effects seen are likely a direct result of changes in smoke exposure in utero. Using a twins based analysis, we link very low birth weight status to adult labor force participation and suggest that via the improvements in birth weight alone, the smoking restriction law in Norway could result in a 0.2 percentage point increase in full time employment by age 28.
Keywords: D62; J13; I38; 330; maternal smoking; smoking bans; very low birth weight; Rauchen; Mütter; Kinder; Gesundheit; Schätzung; Norwegen